Exploring the Phenomenon of Zero Waste and Future Cities - Hannon, Jonathon; Zaman, Atiq (2018)
The evolving phenomenon of zero waste encompasses the theory, practice, and learning of individuals, families, businesses, communities, and government organisations, responding to perceptions of crisis and failure around conventional waste management. The diverse and growing body of international zero waste experience, can be portrayed as both, an entirely new and alternative waste management paradigm, and or, interpreted as overlapping, extending, and synergetic with a general evolution towards more sustainable waste/resource management practices. Combining the terms zero and waste provokes creative, intellectual, and pragmatic tensions, which provide a contemporary axis for necessary debate and innovation in this sphere of resource management. This commentary draws on an interdisciplinary perspective and utilises some elements of the critique of zero waste, as a lens to examine and better understand this heterogeneous global community of practice. In particular, how the concept and implementation of a zero waste goal can increase community engagement and be a catalyst for the design and management of a more circular urban metabolism and hence, more adaptive, resilient, and sustainable future (zero waste) cities.